Readings in sexualities from Africa - Spronk, Rachel; Hendriks, Thomas (Bloomington, Indiana : Indiana University Press, in association with the International African Institute, 2020)
Images and stories about African sexuality abound in today's globalized media. Frequently old stereotypes and popular opinion inform these stories, and sex in the media is predominately approached as a problem in need of solutions and intervention. The authors gathered here refuse an easy characterization of African sexuality and instead seek to understand the various erotic realities, sexual practices, and gendered changes taking place across the continent. They present a nuanced and comprehensive overview of the field of sex and sexuality in Africa to serve as a guide though the quickly expanding literature. This collection offers a set of texts that use sexuality as a prism for studying how communities coalesce against the canvas of larger political and economic contexts and how personal lives evolve therein. Scholars working in Africa, the U.S., and Europe reflect on issues of representation, health and bio-politics, same-sex relationships and identity, transactional economies of sex, religion and tradition, and the importance of pleasure and agency. This multidimensional reader provides a comprehensive view of sexuality from an African perspective.
Introduction: Reading "sexualities" from "Africa" / Rachel Spronk and Thomas Hendriks -- Is there a distinct African sexuality? A critical response to Caldwell / Beth Maina Ahlberg -- Which bodies matter? Feminism, poststructuralism. race, and the curious theoretical odyssey of the "Hottentot Venus" / Zine Magubane -- "Bisexuality" and the politics of normal African ethnography / Marc Epprecht -- On being area-studied: a litany of complaint / Keguro Macharia -- Dangerous aphrodisiac, restless sexuality: venereal disease, biomedicine, and protectionism in colonial Lagos, Nigeria / Saheed Aderinto -- Irua Ria Atumia and anticolonial struggles among the Gĩkũyũ of Kenya: a counternarrative on "female genital mutilation" / Wairimũ Ngarũiya Njambi -- "These women, they force us to rape them": rape as narrative of social control in postapartheid South Africa / Helen Moffett -- "Transparent sexualities": sexual openness, HIV disclosure, and the governmentality of sexuality in South Africa / Marian Burchardt -- A note on "woman marriage" in Dahomey / Melville Jean Herskovits -- Sexual inversion among the Azande / Edward E. Evans-Pritchard -- "A man is a man completely and a wife is a wife completely": gender classification and performance among "ladies" and "gents" in Ermelo, Mpumalanga / Graeme Reid -- The imagined homoconference: "activistism" and the politics of indirection / Serena Owusu Dankwa -- The materiality of everyday sex: thinking beyond "prostitution" / Mark Hunter -- On remuneration for homosexual practices in Bamako / Christophe Broqua -- Belonging in ethnocentric economies: adultery, alerity, and ritual in postcolonial Kenya / George Paul Meiu -- The pleasures of the city: masculinity, sexuality, and femininity in Dakar (1997-2000) / Tshikala Kayembe Biaya -- Postcolonial histories of sexuality: the political invention of libidinal African straight / Basile Ndjio -- Homosexuality, politics, and pentecostal nationalism in Zambia / Adriaan S. van Klinken -- "He uses my body": female traditional healers, male ancestors, and transgender in South Africa / Cheryl Stobie -- The sexual potentate: on sodomy, fellatio, and other postcolonial privacies / Achille Mbembe -- Sex life among young people / Jomo Kenyatta -- Eroticism, sensuality, and women's secrets among the Baganda: a critical analysis / Sylvia Tamale -- Sex, food, and female power: discussion of data material from northern Mozambique / Signe Arnfred -- My childhood as an adult molester: a Salt River moffie / Zackie Achmat.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Africa -- Social conditions; Sex -- Africa; Sex -- Social aspects; Sexual orientation; Afrique -- Conditions sociales; Sexualité -- Afrique; Sexualité -- Aspect social; Orientation sexuelle; Sexuality; HEALTH & FITNESS; Sex; Sex -- Social aspects; Sexual orientation; Social conditions; Africa; Sexualverhalten; Afrika; Sexual orientation; Sexual preference; Electronic books